2014
DOI: 10.1098/rspa.2014.0522
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of elastic networks

Abstract: We consider a periodic lattice structure in d = 2 or 3 dimensions with unit cell comprising Z thin elastic members emanating from a similarly situated central node. A general theoretical approach provides an algebraic formula for the effective elasticity of such frameworks. The method yields the effective cubic elastic constants for three-dimensional spacefilling lattices with Z = 4, 6, 8, 12 and 14, the last being the 'stiffest' lattice proposed by Gurtner & Durand (Gurtner & Durand 2014 Proc. R. Soc. A 470,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 30 publications
3
60
0
Order By: Relevance
“…A recent study by A. N. Norris [11] presents a discrete-to-continuum approach to the elastic moduli of different periodic structures, including pentamode, simple cubic, BCC, FCC octet truss and tetrakaidecahedral lattices. We hereafter summarize the main results of such a study, with reference to the unit cell of a d-dimensional lattice that is composed of a number Z of elastic members (rods) and occupies a volume V.…”
Section: Elastic Moduli Of Lattice Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study by A. N. Norris [11] presents a discrete-to-continuum approach to the elastic moduli of different periodic structures, including pentamode, simple cubic, BCC, FCC octet truss and tetrakaidecahedral lattices. We hereafter summarize the main results of such a study, with reference to the unit cell of a d-dimensional lattice that is composed of a number Z of elastic members (rods) and occupies a volume V.…”
Section: Elastic Moduli Of Lattice Materialsmentioning
confidence: 99%
“…With reference to the unit cells examined in [11], it is easily shown that the elastic stiffness tensor that characterize the lattice response at the mesoscopic scale shows cubic symmetry with independent stiffness coefficients 11 12 , C C and 44 C (Voigt notation). Let us introduce the following notations…”
Section: Elastic Moduli Of Lattice Materialsmentioning
confidence: 99%
See 3 more Smart Citations